자폐스펙트럼장애에서 나타나는 퇴행의 임상적인 특징 - 김지순(Ji-Soon Kim); 유희정(Hee-Jeong Yoo); 조인희(In-Hee Cho); 박태원(Tae-Won Park); 손정우(Jung-Woo Son); 정운선(Un-Sun Chung); 신민섭(Min-Sup Shin); 김붕년(Bung-Nyun Kim); 김재원(Jae-Won Kim); 양영희(Young-Hui Yang); 강제욱(Je-Wook Kang); 송숙형(Sook-Hyung Song); et al. (Soa--chʻŏngsonyŏn chŏngsin ŭihak = Journal of child & adolescent psychiatry, 2011)
Pbjective : A significant proportion of children with autism spectrum disorders (ASD) have regression characterized by loss of previously acquired skills. The purpose of this study was to compare demographic, clinical characteristics and autism-related symptomatology of the children who have regression with children who don't have regression. Methods : The subjects with ASD and their unaffected siblings (SIB) were recruited from the Korean Autism Genetic Study Consortium. Typically developing children (TC) were volunteered from community. The subjects were administered the Korean version of Autism Diagnostic Interview-Revised (K-ADI-R) and the Korean version of Autism Diagnostic Observation Schedule (K-ADOS) to diagnose or exclude ASD. Regression was defined on the basis of K-ADI-R data. The Korean version of Vineland Adaptive Behavior Scale (K-VABS), Aberrant Behavior Checklist (K-ABC) and Social Responsiveness Scale (K-SRS) were obtained from their parents. Results : Regression occurred in 8.33% (n=14) of children with ASD (n=168). Any SIB (n=166) and TC (n=53) did not experience regression. Regression was associated with lower IQ and lower score of K-VABS. There was no difference in autism symptom severity and K-ABC, K-SRS scores, between children with ASD who experienced regression and who did not. Conclusion : Regression seems to be a distinctive feature of ASD. Regression is associated with cognitive and more general functions, rather than symptoms specific to autism.